A case of vascular tumour mimicking lymphangioma - Vala, Helena (2016)
Introduction Sarcomas, particularly vascular tumours, can mimic other neoplastic conditions or even inflammatory diseases. Objectives The authors describe an unusual case of vascular tumour, histologically overlapping with benign lymphangioma and liposarcoma. Medical History A 8 year old Shar Pei male dog was presented with a subcutaneous nodule in the chest, measuring 3x2 cm. Material and Methods The sample was fixed in 10 % buffered formalin solution and processed for routine histopathological diagnosis with Haematoxylin and Eosin. A standard Streptavidin-Biotin Complex technique for immunohistochemical evaluation was also performed, using a Polyclonal Rabbit Anti-Human Von Willebrand Factor. Results Macroscopic examination revealed a well circumscribed nodule with homogeneous and brownish appearance and moderate consistency on a cut surface. Microscopic examination revealed clefts and variably-sized vascular spaces, lined by a single layer of spindle cells, with round-to-oval nuclei, small or indistinct nucleoli, small amount of eosinophilic cytoplasm, with endothelial appearance – areas like hemangiosarcoma, interspersed with areas, where these cells appeared to grow directly on thick bundles of dermal collagen, occasionally with erythrocytes – areas like lymphangioma. The stroma was also interspersed with vacuolar cells – areas like liposarcoma. No mitotic figures were seen, however, the presence of very rich cellular areas, with more prominent cells revealing pleomorphism and anisocariosis, were more favour to malignancy Conclusion The authors suggested the diagnosis of vascular neoplasia with unusual features, based on the histopathological diagnosis and immunohistochemistry results, and submit to the discussion, especially for assessment of histological grade and prognosis.